Networked learning for agricultural extension: a framework for analysis and two cases. Issue 5 (20th October 2017) - Kelly, Nick; Bennett, John McLean; Starasts, Ann
ABSTRACT: Purpose: This paper presents economic and pedagogical motivations for adopting information and communications technology (ICT)-mediated learning networks in agricultural education and extension. It proposes a framework for networked learning in agricultural extension and contributes a theoretical and case-based rationale for adopting the networked learning paradigm. Design/methodology/approach: A review of the literature highlights the economic and pedagogical need for adopting a networked learning approach. Two examples are described to instantiate the language for learning networks: a small community of farmers in India and large Twitter community of Australian farmers. Findings: This paper reviews evidence that successful networked learning interventions are already occurring within agricultural extension. It provides a framework for describing these interventions and for helping future designers of learning networks in agricultural extension. Practical implication: Facilitation of learning networks can serve to achieve efficient agricultural extension that connects farmers across distances for constructivist learning. To realize these benefits, designers of learning networks need to consider set design, social design and epistemic design. Theoretical implication: This paper contributes a theoretical framework for designing, implementing and analysing learning networks in agriculture. It does this by integrating existing ideas from networked learning and applying them to the agricultural context through examples. Originality/value: This paper contributes an understanding of the value of networked learning for extension in terms of economic and pedagogical benefits. It provides a language for talking about learning networks that is useful for future researchers and for practitioners.